Particle deposition in a peri-urban Mediterranean forest. (November 2016) - Fares, Silvano; Savi, Flavia; Fusaro, Lina; Conte, Adriano; Salvatori, Elisabetta; Aromolo, Rita; Manes, Fausto
Abstract: Urban and peri-urban forests provide a multitude of Ecosystem Services to the citizens. While the capacity of removing carbon dioxide and gaseous compounds from the atmosphere has been tested, their capacity to sequestrate particles (PM) has been poorly investigated. Mediterranean forest ecosystems are often located nearby or inside large urban areas. This is the case of the city of Rome, Italy, which hosts several urban parks and is surrounded by forested areas. In particular, the Presidential Estate of Castelporziano is a 6000 ha forested area located between the Tyrrhenian coast and the city (25 km downtown of Rome). Under the hypothesis that forests can ameliorate air quality thanks to particle deposition, we measured fluxes of PM1, 2.5 and 10 with fast optical sensors and eddy covariance technique. We found that PM1 is mainly deposited during the central hours of the day, while negligible fluxes were observed for PM 2.5 and 10. A Hybrid Single–Particle Lagrangian Integrated Trajectory model (HYSPLIT v4) simulated PM emission from traffic areas in the city of Rome and showed that a significant portion of PM is removed by vegetation in the days when the plume trajectory meets the urban forest. Graphical abstract: Highlights: A peri-urban Mediteranean forest near the city of Rome is exposed to anthropogenic PM. Bi-directional fluxes of PM were measured in a Holm Oak forest with eddy covariance. The forest is a sink for PM 1 during the central hours of the day while fluxes of PM 2.5 and PM 10 were negligible. HYSPLIT model simulations showed a potential to abate up to 23% of PM 1 from ambient air. Abstract : Eddy Covariance PM fluxes and a Hybrid Single–Particle Lagrangian Integrated Trajectory model (HYSPLIT) showed that periurban forest can sequestrate PM from the pollution plume transported to the experimental site from the city of Rome.